A case of pediatric lymphomatoid papulosis treated with photodynamic therapy and narrowband ultraviolet B. Issue 5 (3rd July 2020) - Snider, Sam; Costello, Collin M.; Ederaine, Sophia; Besch‐Stokes, Jake; Severson, Kevin J.; DiCaudo, David J.; Pittelkow, Mark R.; Mangold, Aaron R.
Abstract: We report a case of a 13‐year‐old boy with extensive lymphomatoid papulosis (LyP) involving his elbows, forearms, proximal thighs, and right hip, with treatment‐resistant nodules on his right forearm. He was treated with full‐body narrowband ultraviolet B and targeted photodynamic therapy (PDT) with 20% aminolevulinic acid (ALA). After two months, there was complete resolution of the right forearm nodules. Due to its minimal toxicity, PDT offers unique advantages and may be considered for pediatric LyP patients with symptomatic, localized disease resistant to conventional treatments.